New light on old fingermarks: The detection of historic latent fingermarks on old paper documents using 1,2-indanedione/zinc - Bouzin, Jemmy T.; Merendino, Jason; Bleay, S.M.; Sauzier, Georgina; Lewis, Simon (2020)
This study explores trends in the effectiveness of 1,2-indandione/zinc chloride (IND/Zn) for visualizing latent fingermarks on paper substrates of various ages. Preliminary investigation of contemporaneous documents showed that high quality fingermarks could be deposited through incidental handling, although smudging and overlapping were evident. IND/Zn was then applied to incidentally handled documents up to 80 years old and successfully developed potentially identifiable fingermarks, significantly increasing the established timescale for fingermark detection with amino acid sensitive reagents. The results indicate that IND/Zn remains effective over longer periods than has been previously demonstrated, although a comparison between documents of different ages suggest that progressive diffusion of the target amino acids occurs over time, affecting the proportion of potentially identifiable marks. The findings of this study reinforce the applicability of IND/Zn for the detection of historic latent fingermarks on old paper documents.